Cybersecurity talent shortage - Tomić Rotim, Silvana; Komnenić, Višnja (2020)
Different reports show that organizations face a number of hurdles in their efforts to better protect sensitive data. Most frequently mentioned is the challenge of enforcing security policy across the data lifecycle (57%), followed by lack of expert staff (50%), and lack of budget (48%). This article includes the statistics regarding cybersecurity threats and attacks, professionals’ shortage and the expected knowledge, skills and experience for doing this kind of job. Also the article offers some possible solutions for solving this problem, as well as the advantages and disadvantages of different options.
Bibliografija: 10 jed.
Abstract.
Keywords: Cyber sigurnost -- Zaštita podataka -- Sigurnost